Oxidative stress as a potential target in acute kidney injury - Tomsa, Anamaria Magdalena; Alexa, Alexandru Leonard; Junie, Monica Lia; Rachisan, Andreea Liana; Ciumarnean, Lorena (PeerJ, 2019)
Background Acute kidney injury (AKI) is a major problem for health systems being directly related to short and long-term morbidity and mortality. In the last years, the incidence of AKI has been increasing. AKI and chronic kidney disease (CKD) are closely interconnected, with a growing rate of CKD linked to repeated and severe episodes of AKI. AKI and CKD can occur also secondary to imbalanced oxidative stress (OS) reactions, inflammation, and apoptosis. The kidney is particularly sensitive to OS. OS is known as a crucial pathogenetic factor in cellular damage, with a direct role in initiation, development, and progression of AKI. The aim of this review is to focus on the pathogenetic role of OS in AKI in order to gain a better understanding. We exposed the potential relationships between OS and the perturbation of renal function and we also presented the redox-dependent factors that can contribute to early kidney injury. In the last decades, promising advances have been made in understanding the pathophysiology of AKI and its consequences, but more studies are needed in order to develop new therapies that can address OS and oxidative damage in early stages of AKI. Methods We searched PubMed for relevant articles published up to May 2019. In this review we incorporated data from different types of studies, including observational and experimental, both in vivo and in vitro, studies that provided information about OS in the pathophysiology of AKI. Results The results show that OS plays a major key role in the initiation and development of AKI, providing the chance to find new targets that can be therapeutically addressed. Discussion Acute kidney injury represents a major health issue that is still not fully understood. Research in this area still provides new useful data that can help obtain a better management of the patient. OS represents a major focus point in many studies, and a better understanding of its implications in AKI might offer the chance to fight new therapeutic strategies.
Keywords: Acute kidney injury; Oxidative stress; Physiopathology; Reactive oxygen species; Mithocondria